2011
DOI: 10.1007/bf01616442
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of safety and efficacy of sublingual captopril with sublingual nifedipine in hypertensive crisis

Abstract: Sublingual nifedipine is commonly used in hypertensive crisis, however, it may result in several adverse effects such as reflex tachycardia, headache, and flushing. Research is continuing to find a new drug that has the same efficiency and fewer side effects. Sublingual captopril, a new preparation of angiotensin-converting enzyme inhibitor, lowers blood pressure. It is not known whether it is effective in these emergent clinical settings. Therefore we designed a randomized, double-blind study to compare the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Sixteen randomized controlled trials [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] (769 patients) met the inclusion criteria for this review. We excluded 58 clinical trials for several reasons:…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Sixteen randomized controlled trials [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] (769 patients) met the inclusion criteria for this review. We excluded 58 clinical trials for several reasons:…”
Section: Resultsmentioning
confidence: 99%
“…Adverse effects: There were significant differences favoring participants receiving ACEi drugs, compared with CCB drugs, concerning adverse effects such as flushing 15,16,19,22,29 (risk ratio 0.22; 95% confidence interval 0.07 to 0.72) and headache 16,19,22,28,29 (risk ratio 0.34; 95% confidence interval 0.13 to 0.92) (Figures 1 and 2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both oral and sublingual captopril is a common used in emergency room. There are many studies demonstrated that sublingual captopril was effective for lowering blood pressure in patients with hypertensive urgency [23] and emergency [24][25][26][27]; however, some studies observed that rapid and fast blood pressure reduction by sublingual route was harmful [28,29]. In term of efficacy, there were conflict results of the efficacy between oral and sublingual route of captopril.…”
Section: Discussionmentioning
confidence: 99%